2008
DOI: 10.1097/hjr.0b013e328300271f
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid profile of patients referred to a cardiac rehabilitation program

Abstract: Comprehensive CRP improves TC, TG, LDL, and HDL in Iranian patients with cardiovascular disease even without antilipid drugs, and antilipid therapy can boost this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
11
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
5
11
2
1
Order By: Relevance
“…Yusuf et al [29] showed that for an LDL cholesterol reduction of 1 mmol/l (38.7 mg/dl) there is a 21% reduction in cardiovascular events. Our patients experienced a 22% decrease in LDL levels after exercise training, a slightly larger improvement than what was found in other studies [9,30] . This positive effect of exercise was seen on top of statin therapy, which most patients were already taking at the beginning of the program (and that did not change significantly during phase II).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Yusuf et al [29] showed that for an LDL cholesterol reduction of 1 mmol/l (38.7 mg/dl) there is a 21% reduction in cardiovascular events. Our patients experienced a 22% decrease in LDL levels after exercise training, a slightly larger improvement than what was found in other studies [9,30] . This positive effect of exercise was seen on top of statin therapy, which most patients were already taking at the beginning of the program (and that did not change significantly during phase II).…”
Section: Discussioncontrasting
confidence: 50%
“…It has also been shown to improve the metabolic profile and control of risk factors, the quality of life and the functional capacity of these patients [9] . However, CR is still underutilized, across all Europe, and particularly in Portugal [10] .…”
mentioning
confidence: 99%
“…Cardiac rehabilitation provides a substantial benefit in management of major CV risk factors including lipid profile and BP in patients with CV diseases 36. The 3- to 4-week inpatient cardiac rehabilitation in Germany is designed according to the recommendations of national and European Society of Cardiology guidelines37 and offers the opportunity not only to monitor patients after ACS but also to reinforce secondary preventive approaches in the long-term treatment of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Inúmeros estudos vêm relatando os benefícios da reabilitação cardíaca (RC) na diminuição da morbidade e mortalidade de pacientes submetidos à cirurgia de revascularização miocárdica (CRM) e doença aterosclerótica coronariana (DAC) 1,2 . Segundo, o Serviço de Saúde Pú-blica dos EUA, a reabilitação cardíaca é definida como um programa que envolve avaliação médica, exercícios supervisionados, educação e orientação para pacientes com doenças cardíacas 3 .…”
Section: Introductionunclassified